THE MATERIAL CONTENT OF REGIONAL REGULATIONS AS THE CONCRETIZATION OF THE LIVING LEGAL SYSTEM IN SOCIETY (ADAT LAW) BASED ON ARTICLE 2 OF THE INDONESIAN PENAL CODE (KUHP) 2023 - Sumika Putri, Nella (Faculty of Law Universitas Padjadjaran, 2023)
Article 2 of Law Number 1 of 2023 regarding the Criminal Code (“KUHP 2023”) not only leaves problems in the context of legality, but also includes mechanisms for the law enforcement process, particularly regarding the measurement of the applicability of Indonesian customary law (“Adat Law”) through regional regulations. One issue that has arisen is the lack of standardized content material that must be regulated in regional regulations in order to determine the applicability of Adat (criminal) Law. This article will analyze to what extent the standard of “law that applies in the place where the law lives” and to what extent the regional regulation regulating “living law” in the perspective of law enforcement prosecutes the perpetrator. The results show that regional regulation can be used as a basis for determining the recognition of Adat Law, but there is no common standard for how to recognize Adat Law under regional regulation. As the concrete of Article 2 Indonesian Penal Code 2023, regional regulation must explicitly regulate the scope of Adat Law (criminal) application related to territorial, personal and protection principles. Meanwhile, in the case of the prohibition act and penal sanction, it needs further studies because Adat Law has no separation between criminal and civil matters.